Linear and multivalent PEGylation of the tobacco mosaic virus and the effects on its biological properties - Caballero, Reca Marian; González-Gamboa, Ivonne; Craig, Stephen L.; Steinmetz, Nicole F. (Frontiers in Virology, 2023)
Plant virus-based nanoparticles (VNPs) offer a bioinspired approach to the delivery of drugs and imaging agents. The chemical addressability, biocompatibility, and scalable manufacturability of VNPs make them a promising alternative to synthetic delivery platforms. However, VNPs, just like other proteinaceous or synthetic nanoparticles (NPs), are readily recognized and cleared by the immune system and mechanisms such as opsonization and phagocytosis. Shielding strategies, such as PEGylation, are commonly used to mitigate premature NP clearance. Here, we investigated polyethylene glycol (PEG) coatings on the tobacco mosaic virus (TMV), which was used as a model nanocarrier system. Specifically, we evaluated the effects of linear and multivalent PEG coatings at varying chain lengths on serum protein adsorption, antibody recognition, and macrophage uptake. Linear and multivalent PEGs of molecular weights 2,000 and 5,000 Da were successfully grafted onto the TMV at ≈ 20%–60% conjugation efficiencies, and the degree of cross-linking as a function of PEG valency and length was determined. PEGylation resulted in the modulation of TMV–macrophage interactions and reduced corona formation as well as antibody recognition. Linear and multivalent PEG 5,000 formulations (but not PEG 2,000 formulations) reduced α-TMV antibody recognition, whereas shorter, multivalent PEG coatings significantly reduced α-PEG recognition—this highlights an interesting interplay between the NP and the PEG itself in potential antigenicity and should be an important consideration in PEGylation strategies. This work provides insight into the PEGylation of VNPs, which may improve the possibility of their implementation in clinical applications.